On some taxonomic and nomenclatural problems in Indian species of the genus Oligodon Fitzinger, 1826 (Squamata: Colubridae) - David, Patrick; Das, Idraneil; Vogel, G. (Zootaxa, 2011)
This paper deals with three nomenclatural and taxonomic problems affecting two species groups of the colubrid snake genus Oligodon Fitzinger, 1826: (i) A neotype is formally designated for Coronella cyclura Cantor, 1839, associating this specific nomen with populations from India, Bangladesh and Myanmar with 19 scale rows at midbody; (ii) Oligodon kheriensis Acharji & Ray, 1936 is shown to be a valid species of the Oligodon cyclurus group occurring in northern India and Nepal; (iii) The type-locality of Simotes multifasciatus Jan & Sordelli, 1865 is shown to be Sultanpur, India. This taxon is considered a synonym of Oligodon cinereus (Günther, 1864). The range of this species in India is extended. The status of specimens of Oligodon cinereus from India and Myanmar is briefly discussed. Specimens from Thailand identified as Oligodon cinereus multifasciatus and Oligodon cinereus swinhonis (Günther, 1864) are referred to Oligodon joynsoni (Smith, 1917). India is home to at least 21 species of the genus Oligodon, an updated list of which is provided.